2018
DOI: 10.1021/acs.analchem.8b01963
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of Fragmentation Pathways in Protonated N-Acetylhexosamines

Abstract: Structural characterization of carbohydrates by mass spectrometry necessitates a detailed understanding of their gas phase behavior, particularly for protonated carbohydrates that can undergo complex structural rearrangements during fragmentation. Here we utilize tandem mass spectrometry, isotopic labeling, gas-phase hydrogen/deuterium exchange, and ion mobility measurements to characterize structures of the various product ions of protonated N-acetylhexosamines. Following the facile loss of the reducing end h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 46 publications
6
26
0
Order By: Relevance
“…Our combined data offer a mechanistic explanation of the dissociation chemistry consistent with Nilsson and co-workers 69,71 conclusion that the m/z 126 and 144 peaks "correspond to entirely different structures, which have followed completely different decomposition pathways" 71 . Consistent with the present dataset, Mookherjee et al 72 recently provided evidence that cast doubt on the mechanism and product ion structure originally proposed by Yu et al 71 for the key m/z 126 peak using model protonated HexNAc analytes rather than peptidoglycans.…”
Section: Consecutive Dissociation Of the Furanose Oxazolinium B1 Ion: Formation Of M/z 126supporting
confidence: 83%
“…Our combined data offer a mechanistic explanation of the dissociation chemistry consistent with Nilsson and co-workers 69,71 conclusion that the m/z 126 and 144 peaks "correspond to entirely different structures, which have followed completely different decomposition pathways" 71 . Consistent with the present dataset, Mookherjee et al 72 recently provided evidence that cast doubt on the mechanism and product ion structure originally proposed by Yu et al 71 for the key m/z 126 peak using model protonated HexNAc analytes rather than peptidoglycans.…”
Section: Consecutive Dissociation Of the Furanose Oxazolinium B1 Ion: Formation Of M/z 126supporting
confidence: 83%
“…This is thought to arise from the generation of different isomeric fragment ion structures, whose ensemble is affected by the structure of the precursor. Similar 'memory effects' were also observed by both IM-MS and MS n relative fragmentation propensities even after multi-stage MS 22 . Here we sought to characterize the fragmentation patterns within larger oligosaccharides and the structural disposition of the resulting fragment ions.…”
Section: Introductionsupporting
confidence: 66%
“…Similarly, the (1-6) linked structure cannot form the O6-C1 bridged structure. Previous mapping of the fragmentation pathways of GlcNAc revealed that the 204 ion dissociates through two competing pathways to generate either: 1) primarily m/z 186 through water loss; or 2) m/z 126 through a ring rearrangement reaction 22 . The O4-C1 bridge structure was proposed to initiate the ring rearrangement to form m/z 126.…”
Section: Structural Rationalization Of Linkage Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…1E, F) was performed on all six disaccharides to fragment the GlcNAc (m/z 204) remnant, probing for signature CID fragmentation patterns. In addition to m/z 186, 168, 144 and 138, the MS 4 (384→366→204→) spectra of all disaccharides yield m/z 126 and 84 which are primary and secondary products of m/z 204 22 (Figs. 1E, F).…”
Section: Characterization Of Linkage and Anomeric Memory By Tandem Msmentioning
confidence: 99%